O-032 Predictors of Poor Outcomes Despite Successful Recanalization in Patients with Acute Ischemic Stroke. (26th July 2014) - Linfante, I; Dabus, G; Starosciak, A; Castonguay, A; Gupta, R; Sun, C; Martin, C; Holloway, W; Mueller-Kronast, N; English, J; Malisch, T; Marden, F; et al.
Abstract : Background: Recanalization of the occluded artery is a powerful predictor of good outcome in acute ischemic stroke secondary to large artery occlusions. Mechanical thrombectomy with stent-trievers results in higher recanalization rates and better outcomes compared to previous devices. However, despite successful recanalization rates (Treatment in Cerebral Infarction, TICI, score ≥ 2b) between 70 and 90%, good clinical outcomes assessed by modified Rankin Scale (mRS ≥ 2 is present in 40–50% of patients. We aimed to evaluate predictors of poor outcomes (mRS ≥ 2) despite successful recanalization (TICI ≥ 2b) in the acute stroke patients treated with the Solitaire device of the North American Solitaire Stent Retriever Acute Stroke (NASA) registry. Methods: The NASA registry is a multicenter, non-sponsored, physician-conducted, post-marketing registry on the use of SOLITAIRE FR device in 354 acute, large vessels, ischemic stroke patients. Logistic regression was used to evaluate patient characteristics and treatment parameters for association with 90-day mRS score of 0–2 (good outcome) versus 3–6 (poor outcome) within patients who were recanalised successfully (Thrombolysis in Cerebral Infarction or TICI score 2b-3). Univariate tests were followed by development of a multivariable model based on stepwise selection with entry and retention criteria of p < 0.05 from the set of factors with at least marginal significance (p ≤ 0.10) on univariate analysis. The c-statistic was calculated as a measure of predictive power. Results: Out of 354 patients, 256 (72.3%) were successfully recanalised (TICI ≥ 2b). Based on 90-day mRS score for 234 of these patients, there were 116 (49.6%) with mRS ≥2. Univariate analysis identified increased risk of mRS ≥2 for each of the following: age ≥ 80 years (upper quartile of data), occlusion site other than M1/M2, NIH Stroke Scale (NIHSS) score ≥ 18 (median), history of diabetes mellitus (DM), TICI = 2b, use of rescue therapy, not using a balloon-guided catheter (BCG) or intravenous tissue plasminogen activator (IV t-PA), and time to recanalization > 30 min (all p ≤ 0.05). Three or more passes was marginally significant (p = 0.097). In multivariable analysis, age ≥80 years, site other than M1/M2, initial NIHSS ≥18, DM, absence of IVtPA, use of rescue therapy and three or more passes were significant independent predictors of poor 90-day outcome in a model with good predictive power (c-index = 0.80). Conclusions: Age, occlusion site, high NIHSS, diabetes, not receiving IVtPA, use of rescue therapy and three or more passes, were associated with poor 90-day outcome despite successful recanalization. Disclosures: I. Linfante: None. G. Dabus: None. A. Starosciak: None. A. Castonguay: None. R. Gupta: None. C. Sun: None. C. Martin: None. W. Holloway: None. N. Mueller-Kronast: None. J. English: None. T. Malisch: None. F. Marden: None. H. Bozorgchami: None. A. Xavier: None. A. Rai: None. M. Froehler: None. A. Badruddin: None. T. Nguyen: None. M. Taqi: None. M. Abraham: None. V. Janardhan: None. H. Shaltoni: None. R. Novakovic: None. A. Yoo: None. O. Zaidat: None.